The Color of Value: English as an Index of Racialization on the Brazil-Guyana border - Fonseca, Natália Barroncas da; de Moraes Garcez, Pedro (Íkala, Revista de Lenguaje y Cultura, 2025)
This article discusses language ideological work in the discourse of Guyanese migrants on the Brazil-Guyana border regarding their sociolinguistic repertoires. An analysis of interviews with racialized Guyanese migrants in Brazil reveals the use and exchange values attributed by them to the linguistic resource “English.” Drawing on the theoretical and methodological framework of studies on language in advanced capitalism, language ideologies, racialized language ideologies, and use-and-exchange value, we examine excerpts from interviews with Guyanese migrants living in the Brazil-Guyana border area about their linguistic repertoire, with an emphasis on “English.” The analysis shows that, for different references to “English,” there are different valuations. The use value of references to English is minimal, due to the feeling of shame in speaking it, marked by raciolinguistic ideologies. As for English on a local scale, its exchange value seems lower than expected for this “global language,” as participants do not report using it for economic advantage or social prestige. Thus, we broaden the understanding of the intersections between language and race by showing how, in this economically peripheral setting, raciolinguistic ideologies constrain the attribution of value to a linguistic resource that is otherwise globally valued.